Design of Health, Safety, and Environment Digital Application with Android-Based User Interface - Ely Purnawati; Alif Yahya Syafa'at; Dimas Didan Febianto; Dwiana Sari; Laily Farkhah Adhimah (Sistemasi: Jurnal Sistem Informasi, 2023)
Health, Safety, and Environment (HSE) also known as Occupational Health and Safety (K3) is an important matter that must be considered by all parties while in the work environment. Several companies or agencies have implemented an HSE management system, both manually and digitally. Unfortunately, however, accidents continue to occur, so support and encouragement from all parties is still needed to improve the HSE management system. The purpose of this research is to design an application that can help users such as HSE officers or companies/agencies in HSE management. The method used is Waterfall. The results obtained were the successful creation of a HSE management application in digital format that named "K3 Agent" with an Android-based user interface. In testing the use of the application was successfully run and can be used to assist work such as making analyses, reports, guidelines and other requirements related to HSE.